NEURO-DASH: Inovasi Dashboard Surveilans Psikologis Berbasis AI untuk Memetakan Titik Rawan Stres Akademik di Lingkungan Kawasan Kampus - Stela Virginia Sirait; Ronny; Grace Ade Christy S (Psychology Journal of Mental Health, 2025)
The surge in mental health crises in higher education, exacerbated by academic pressure, has become an urgent global issue. Data from the WHO (2022) indicates that more than 60% of the student population in various countries report excessive anxiety, while research in Indonesia by the Indonesian Clinical Psychologists Association (2023) highlights that 8 out of 10 students experience academic stress with a negative impact on their performance. This situation not only threatens the quality of life of individuals but also hinders the achievement of the Sustainable Development Goals (SDGs), particularly points 3 (Good Health and Well-being) and 4 (Quality Education). Therefore, this paper aims to design and propose “NEURO-DASH,” an AI-based psychological surveillance dashboard innovation to map real-time academic stress hotspots on campus. The design methodology uses the SMART (Specific, Measurable, Achievable, Relevant, Time bound) approach integrated with secondary data analysis from literature studies and government mental health data repositories. The NEURO-DASH system is equipped with key features such as Stress Heatmap, Predictive Analytics, Early Alert System, and Interactive Dashboard. It is hoped that NEURO-DASH can become a strategic solution for campus policymakers to carry out targeted data based interventions, support the creation of a healthy and productive academic environment, and contribute directly to the achievement of SDGs in the education sector.